INTERNATIONAL EXPERIENCE WITH 7-VALENT PNEUMOCOCCAL CONJUGATE VACCINE - David G. McIntosh (Педиатрическая фармакология, 2009)
The article is devoted to one of the serious problems of the today's medicine — pneumococcal infection. The authors show its importance for public health in terms of its influence upon infant and child mortality and in validization. They provide a comparative characteristic of pneumococcal vaccines used in the world. The article describes the efficiency and experience of immunizing children with a 7_valent conjugate pneumococcal vaccine in national programs that serve as a basis for recommendations on the prevention of pneumococcal infection given by the World Health Organization.Key words: pneumococcal infection, 7-valent conjugate pneumococcal vaccine, national immunization programs, children.